2015
DOI: 10.1093/nar/gkv932
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Coupling Analysis of nucleotide coevolution facilitates RNA secondary and tertiary structure prediction

Abstract: Despite the biological importance of non-coding RNA, their structural characterization remains challenging. Making use of the rapidly growing sequence databases, we analyze nucleotide coevolution across homologous sequences via Direct-Coupling Analysis to detect nucleotide-nucleotide contacts. For a representative set of riboswitches, we show that the results of Direct-Coupling Analysis in combination with a generalized Nussinov algorithm systematically improve the results of RNA secondary structure prediction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
169
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(184 citation statements)
references
References 56 publications
3
169
0
Order By: Relevance
“…RNAsnap-prof is used to illustrate if sequence conservation information contained in multiple sequence alignment is useful for more accurate determination of tertiary structural properties. A significant increase in the PCC values between predicted and actual ASAs from 0.54 to 0.63 by using the sequence profile confirmed that an RNA base can be conserved for its tertiary structural role (Capriotti and Marti-Renom 2010;De Leonardis et al 2015). Sequence conservation in RNA secondary structure (Gruber et al 2008;Gu et al 2014) has also been studied and used for secondary structure prediction (Rivas 2013;Sharma et al 2014;De Leonardis et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…RNAsnap-prof is used to illustrate if sequence conservation information contained in multiple sequence alignment is useful for more accurate determination of tertiary structural properties. A significant increase in the PCC values between predicted and actual ASAs from 0.54 to 0.63 by using the sequence profile confirmed that an RNA base can be conserved for its tertiary structural role (Capriotti and Marti-Renom 2010;De Leonardis et al 2015). Sequence conservation in RNA secondary structure (Gruber et al 2008;Gu et al 2014) has also been studied and used for secondary structure prediction (Rivas 2013;Sharma et al 2014;De Leonardis et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…The Direct-Coupling Analysis (DCA) has been proposed to disentangle such indirect effects from direct (i.e. epistatic) couplings [10] , allowing prediction of native contacts of protein structures, protein-protein interactions and RNA structures, [11] and the likelihood model underlying them has also been shown to be correlated with protein stability [12] . Indeed, this type of analysis has been used to help design targeted single-point sequence variants [13] .…”
mentioning
confidence: 99%
“…In contrast, our novel rnaDCA is able to extract tertiary contacts from genomic data. We further demonstrate that these tertiary contacts are sufficient to systematically improve tertiary RNA prediction quality [4]. Considering the large gap of known ncRNA sequences to experimentally resolved tertiary structures, we are convinced that this will significantly impact all structural RNA related research.…”
Section: -Platmentioning
confidence: 63%
“…
methylammonium, acetate and water [4]. With the removal of the previous ambiguity brought by using water as both the hydrogen-bond donor and acceptor fragment [2], improved screening results are seen using targets in the DUD database in the extended SILCS-Pharm method.
…”
mentioning
confidence: 99%